Antiinflammatory Activity of Albizia Lebbek (L.) Benth. Stem Bark Extract - K. Jangra, Ashwani; Kumar Goel, Kapil; Nautiyal, Vinod; A. Jangra, Neetu; Manjusha (Asian Journal of Chemistry, 2012)
Albizia lebbek stem bark powder was extracted with petroleum ether, chloroform and alcohol by using soxhlet apparatus. All the extracts were screened for the antiinflammatory activity by measuring the reduction in carrageenan induced hind paw edema. The potency of each extract was compared with each other and standard drug diclofenac sodium for antiinflammatory activity. The maximum antiinflammatory activity was observed in petroleum extract followed by chloroform extract.